(untitled) (Journal of Buffalo Science, 2024)
The objective of the current investigation was to provide a comprehensive characterisation of an Arcanobacterium isolate derived from Bubalus bubalis. The confirmation of the species identity of Arcanobacterium sp. 15/M226/2/9 in this study was achieved by examining phenotypic characteristics and phylogenetic analysis. These analyses involved determining hemolysis on Columbia sheep blood agar and biochemical parameters using the Api-Coryne test kit, MALDI-TOF MS, and partial sequencing of the universal gene encompassing the 16S ribosomal RNA (rRNA) gene, the 16S-23S rDNA intergenic spacer region (ISR), and the two housekeeping genes rpoB and gap. Species classification based on sequencing of the 16S rRNA gene and the ISR revealed a sequence identity of 98.7% each between Arcanobacterium sp. 15/M226/2/9 and A. bovis reference strain C605018/01/1T. In addition, for the other target genes, rpoB and gap, the concordance was 96.6% and 98.8%, respectively. The present study showed that 15/M226/2/9 isolated from B. bubalis could be a novel species.